Implementasi Peraturan Menteri Keuangan No. 76 Tahun 2008 tentang Pedoman Akuntansi dan Pelaporan Keuangan Badan Layanan Umum di Pusat Bisnis UIN Sunan Ampel Surabaya - Adrianto, Anas (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2019)
This journal aims to find out how the implementation of the Minister of Finance Regulation No. 76 of 2008 concerning Accounting and Financial Reporting Guidelines for public service agencies in the operationalization of any obstacles experienced by the Business Center in presenting financial reports in accordance with PMK No. 76 of 2008 concerning Accounting and Financial Reporting Guidelines of public service agencies. The research methodology used is a qualitative approach with a type of case study research approach. Data collection was carried out through interviews with several informants. Then analyzed using descriptive analysis methods. The results of this study are in the presentation of financial statements, the Business Center has made financial reports in accordance with Minister of Finance Regulation No. 76 of 2008, only the Business Center has not presented Notes to Financial Statements. The constraints experienced by the Business Center in presenting financial reports in accordance with the Minister of Finance Regulation No.76 are those that are inadequate and do not yet have the ability to prepare financial statements.